EGFR/FOXO3A/LXR-α Axis Promotes Prostate Cancer Proliferation and Metastasis and Dual-Targeting LXR-α/EGFR Shows Synthetic Lethality - Chen, Tingting; Xu, Jie; Fu, Weihua (Frontiers in Oncology, 2020)
Prostate cancer is the second leading cause of cancer-related death in men. Early prostate cancer has a high five-year survival rate. However, the five-year survival rate is low in progressive prostate cancer, manifesting as bone metastasis. The EGF receptor overexpression increases during disease progression and in the development of castration-resistant disease, and may be a potential therapeutic target. Liver X receptors are ligand‐dependent nuclear receptor transcription factors and consist of two subtypes: LXR-α and LXR-β, which can inhibit tumor growth in various cancer cells. We revealed that LXR-α , but not for LXR-β, was reduced in prostate cancer tissues compared with adjacent normal tissues. LXRs agonist GW3965 enhanced the inhibitory action of LXR-α on the proliferation and metastasis of prostate cancer cells. Furthermore, our results support the notion that LXR-α is regulated by EGFR/AKT/FOXO3A pathway. As an EGFR inhibitor, Afatinib could weak AKT activation and increase the expression level of FOXO3A in prostate cancer. In addition, we indicated that combination of Afatinib and GW3965 simultaneously increased and activated LXR-α, which led to increase of tumor suppressors, and eventually inhibited tumor progression. Therefore, combination of EGFR inhibitor and LXRs agonist may become a potential treatment strategy for prostate cancer, especially metastatic prostate cancer.